Attaining the Millennium Development Goals in Pakistan - World Bank (Washington, DC, 2014)
This report focuses on the attainment of four major human development-related Millennium Development Goals (MDGs) by Pakistan and its main sub-national units - infant mortality, child malnutrition, schooling enrollment and completion, and gender disparities in schooling. The selection of these MDGs for detailed analysis was based in large part on the availability of reliable sub-national data. This paper includes the following headings: introduction; infant and child mortality in Pakistan; child malnutrition; primary school enrollment; primary school completion; gender disparity in child schooling; and conclusions.